1995
DOI: 10.1029/95jd01222
|View full text |Cite
|
Sign up to set email alerts
|

Volcanic sulfur dioxide measurements from the total ozone mapping spectrometer instruments

Abstract: The total ozone mapping spectrometer (TOMS), first flown on the Nimbus 7 satellite, has delivered an unanticipated set of unique information about volcanic plumes because of its contiguous spatial mapping and use of UV wavelengths. The accuracies of TOMS sulfur dioxide retrievals, volcanic plume masses, and eruption totals under low‐latitude conditions are evaluated using radiative transfer simulations and error analysis. The retrieval algorithm is a simultaneous solution of the absorption optical depth equati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
242
0
3

Year Published

1997
1997
2016
2016

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 242 publications
(247 citation statements)
references
References 27 publications
2
242
0
3
Order By: Relevance
“…[3] SO 2 from volcanic eruptions has also been observed from space [e.g., Krueger et al, 1995;Eisinger and Burrows, 1998], but the retrieval of volcanic BrO from satellite measurements has never been reported in literature before. In order to assess how representative the measurements of Bobrowski et al are on a global scale, more measurements of volcanic plumes are needed.…”
Section: Introductionmentioning
confidence: 99%
“…[3] SO 2 from volcanic eruptions has also been observed from space [e.g., Krueger et al, 1995;Eisinger and Burrows, 1998], but the retrieval of volcanic BrO from satellite measurements has never been reported in literature before. In order to assess how representative the measurements of Bobrowski et al are on a global scale, more measurements of volcanic plumes are needed.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, the ratio mass of fluid/(mass of erupted magma) gives the wt % fluid coexisting at depth in the magma chamber. Since the TOMS-based estimates of sulfur may not record the sulfate adsorbed on ashes directly carried down to the ground following eruption, as shown by Varekamp et al [1984] for the E1 Chich6n eruption and as suggested for most other eruptions (J. Luhr, personal communication, 1998), the fluid wt % listed in Table 1 are probaly minimum values (see also Krueger et al [1995] for TOMS limitations in volcanic SO 2 retrievals). For Mount St. Helens, experimental evidence [Rutherford and Devine, 1988] shows that prior to May 18, 1980 eruption the mole fraction of H20 in the fluid phase was 0.67, assuming that the magma was volatile-saturated.…”
mentioning
confidence: 99%
“…Etna [Realmuto et al, 1994]. The EP TOMS data was processed using the standard 4-band inversion technique for SO 2 clouds [Krueger et al, 1995]. Errors for this method are +10%/À20% for a low solar zenith angle assuming sulfate aerosols collocated with SO 2 has a moderate optical depth [Krueger et al, 1995].…”
Section: Methodsmentioning
confidence: 99%